The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/mc.22692
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and metformin‐mediated chemoprevention of oral cancer is associated with inhibition of cancer stem cells

Abstract: Effective chemoprevention is critical for improving outcomes of oral cancer. As single agents, curcumin and metformin are reported to exhibit chemopreventive properties, in vitro as well as in patients with oral cancer. In this study, the chemopreventive efficacy of this drug combination was tested in a 4-nitro quinoline-1-oxide (4NQO) induced mice oral carcinogenesis model. Molecular analysis revealed a cancer stem cell (CSC)-driven oral carcinogenic progression in this model, wherein a progressive increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 51 publications
1
41
0
1
Order By: Relevance
“…The 4NQO model was established and the mice were evaluated at different stages for clinical and histological progression of disease as described previously . Explants from 6th, 14th, and 16th week were successfully propagated in vitro and primary cell lines were developed (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 4NQO model was established and the mice were evaluated at different stages for clinical and histological progression of disease as described previously . Explants from 6th, 14th, and 16th week were successfully propagated in vitro and primary cell lines were developed (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, Notch1 was deregulated in the epithelial cell lines and an inhibition of its activity using GSI led to a significant decrease in CSC and dysplastic profile, indicating its significance in dysplastic progression of oral cancer. Our previous study had demonstrated the anti‐dysplastic, anti‐CSC effect of Curcumin and Metformin in the dysplastic cells, Notch1 downregulation is one of the downstream effects of this treatment, in addition to the inhibition of multiple other pathways. Whether addition of PZ0187 to either of these drugs/combination will increase the effect remains to be explored.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations